Student engagement and attendance are central mechanisms interacting with inclusive and equitable quality education: Evidence from Afghanistan and Pakistan - Trani, Jean-Francois; Hart, Robbie (PloS one, 2023)
Despite considerable progress in the field of education science, there is currently no consensus on the components that define inclusive and equitable quality education, how they are articulated with one another, and what are the best interventions to foster inclusive and equitable quality education. Current research investigates separately components of what appears to be a complex dynamic system with feedback interactions. To characterize this system and identify structures that encompass inclusive and equitable quality education, we used a community-based system dynamics approach. This approach hypothesizes that community perceptions of the local school system is essential to define it. We therefore conducted 648 participatory Group Model Building workshops with school stakeholders (children, teachers, parents and members of school management committees) resulting in as many models in 99 schools of Afghanistan and Pakistan. To identify common components across models built by participants in two waves of schools’ model building workshops, we applied techniques from multivariate analysis of ecological communities. Even across wide differences in participants’ situations and roles in the educational process, their models expressed a common reinforcing feedback loop which connected child inclusive and equitable quality education to two other components: 1) child engagement in and motivation for education, and 2) child attendance. Increases in any of these three components were perceived to drive increases in the others. We also found that child focus on learning was commonly expressed as interacting with this generic structure. Any educational reform should simultaneously and primarily embrace learners’ diversity, combine policy principles of ensuring easy equitable access to foster attendance, and promote student interest and engagement in learning through child centered pedagogy and non-discriminatory teaching practices while giving school communities power for implementation.